An econometric analysis of the investment climate and growth potential in Nigeria - Kalu U Christopher; Francis O Nwaigwe (African Journal of Governance and Development, 2013)
The slow economic growth rate experienced by most developing countries, including Nigeria in the late 1970s and the early 1980s, has now manifested itself in the form of macro-economic imbalances, a wide saving/investment disparity, a steep inflationary spiral, and a high debt overhang. Hence, the study examines improving the Nigerian investment climate for enhanced economic growth. The data was sourced from the Central Bank of Nigeria (CBN) Bulletin and National Bureau of Statistics. The level testing results reveal that none of the variables were stationary at its levels. However, the absolute values of the variables in the first-difference is greater than the Mackinnon Critical value as provided by EVIEWS Package, which means that we do not reject the null hypotheses for the non-stationary series. It was observed that there were many reasons for the poor economic performance of the Nigerian economy, among which was the decline in investment rates. It is thus recommended that polices which will improve and encourage investment should be institutionalised, a stable macro-economic framework should be pursued, a favourable fiscal regime should be promoted, and the financial sector strengthened by diversification to achieve investment objectives